Livro de Rpg: As crônicas de Zatzar, o flagelo das Terras Livres - Puga, Natan Batistel [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Neste relatório, será tratado de todos os métodos e ferramentas utilizados na criação de um livro de RPG independente, “As Crônicas de Zatzar, O Flagelo das Terras Livres”. Serão abordados no texto desde o briefing, metodologia, game design, criação de mundo, game design document, ilustrações, identidade visual, diagramação, play-test, entre outros. RPG é um título para jogos que vão além dos tabuleiros, estendendo-se a uma proposta de interpretação e improvisação, como em um exercício de teatro.

In this report, all the methods and tools used in the creation of an independent RPG book, “The Chronicles of Zatzar, The Scourge of the Free Lands,” will be discussed. The text will cover everything from the briefing, methodology, game design, world creation, game design document, illustrations, visual identity, layout, play-testing, among others. RPG is a title for games that go beyond board games, extending to a proposal for interpretation and improvisation, much like a theater exercise.
Rpg book: The Zatzar cronicles, scourge of Folk's Land
Keywords: Diagramação; Editorial; Jogo; Fantasia; Ilustração; Layout; Editorial; Game; Fantasy; Illustration